English Language Learners: Just Job Seekers or Leaders? - Khatri, Man Bahadur (IJRDO- Journal of Educational Research, 2016)
People call English a crazy language but research studies have found people are crazy forEnglish language all over the world. Many people speak English and it has been working as alingua franca in every function in the world where people of different countries/languagebackgrounds are met. Sometimes people are found roaming for jobs in the market aftercompletion of Master’s in English Language Teaching form recognized universities. They arefound quite frustrated. In such cases they are to be envisioned with some good opportunities andmade optimistic, courageous and risk takers. Some people can have good qualification, skillsand desires but they might not have got opportunities. They might have been lacking behindbecause of the lack of access to information, encouragement and guidance. For them, this articlecan become a direction, hope of ray, trail for destination and oasis for optimism. EnglishLanguage Learners can become good entrepreneurs, leaders, counselors, mentors, motivators,administrators and so on. But, not just a job seekers and passive employees in 21st century.